LEGAL PLURALISM AND CUSTOMARY CRIMINAL LAW: COMPARATIVE PERSPECTIVES FROM INDONESIA AND SOUTH AFRICA IN POST-COLONIAL CRIMINAL JUSTICE SYSTEMS - I Made Wirya Darma; I Gede Agus Kurniawan; Jan Alizea Sybelle (Cepalo, 2026)
This study examines legal pluralism in the regulation of customary criminal law through a comparative analysis of Indonesia and South Africa. Using a normative legal method with conceptual, comparative, and statutory approaches, it explores how both countries integrate customary criminal law into their national criminal justice systems. The findings show that both jurisdictions reflect a post-colonial commitment to legal pluralism by incorporating restorative justice grounded in indigenous legal traditions. Indonesia recognizes customary criminal law through Articles 2 and 66 of the New Criminal Code, while South Africa does so through Section 211 of the Constitution and the Traditional Courts Act. Although both systems seek to promote restorative justice and reduce recidivism, they differ in their institutional design and implementation. Indonesia adopts a hierarchical model in which customary sanctions supplement state law, whereas South Africa grants greater autonomy to customary courts. The study recommends implementing comprehensive Government Regulations and harmonizing Regional Regulations in Indonesia to strengthen legal certainty. It also recommends revising South Africa's Traditional Courts framework to improve judicial oversight, gender representation, and evidentiary standards while ensuring compliance with constitutional human rights protections.